Transient temperature field analysis of steel-plate composite (SC) floor under standard fire. (February 2021) - Qian, Chenhui; Huang, Chengjun; Chen, Sijia; Song, Xiaobing
Graphical abstract: Abstract: To evaluate the fire resistance of a structural member, the temperature profile in the cross section of the member needs to be obtained first. Full-scale fire tests have not been conducted on floor systems with steel-plate composite structures, termed SC floors. The traditional finite element analysis does not yield reliable temperature predictions in the steel and concrete of the SC floor under a standard fire. In this paper, the effective thermal properties of concrete in an SC floor are proposed for evaluating the transient temperature field according to the special heat transfer mechanism found by test data. The validity of these effective thermal properties is established by incorporating them into a finite element model and comparing the temperature predictions with data from fire tests. It is shown that the proposed effective thermal properties of concrete provide a good prediction of the temperature field in an SC floor under fire. The derivation process of the effective thermal properties based on the heat transfer analysis makes it possible to expand the scope of its application when the situation is similar to an SC floor.